Synthesis of 5-arylidene meldrum's acid derivatives via one pot isopropylidene malonate with different aryl: aldehdye and amine / Adryana Izzati Adnan, Noor Hidayah Pungot and Nur Ain Nabilah Ash'ari - Adnan, Adryana Izzati; Pungot, Noor Hidayah; Ash'ari, Nur Ain Nabilah (2020)
A series of arylidene Meldrum's acid derivatives at C-5 position were synthesized with excellent yield through Knoevenagel condensation reaction via one pot reaction. This approach is quite convenient and effective as it does not require any catalyst and no further purification needed. Meldrum's acid or its scientific name called (2, 2-dimethyl-1, 3-dioxane-4, 6-dione) has received many tremendous interests from organic researchers. Meldrum's acid has a distinctive ring-opening reaction that enables the compound to be versatile reagent and acts as useful intermediate product to synthesis Meldrum's acid derivatives. Besides, Meldrum's acid has high methylene hydrogen acidity located at C-5. Hence, this unique characteristic of Meldrum's acid allows the molecule to react with various kind of functional groups which include aryl aldehydes and arylamine group. In this research, the synthesis of arylidene of Meldrum's acid through one-pot reactions involved two steps. The first step began with condensation of malonic acid with acetone in acetic anhydride with small quantity of sulfuric acid to produce the core skeleton. The second step was introduced with different of substituents such as aryl aldehydes and arylamine group at position C-5 of Meldrum's acid via Knoevenagel condensation reaction in good yield. All the synthesized Meldrum's acid derivatives were characterized using NMR spectroscopy. Therefore, all the series of arylidene Meldrum's acid derivatives will been explored by using the functional group interconversion reactions for potential of biological screening.